Detecting Phase Shifts in Surface Plasmon Resonance: A Review. (4th August 2011) - Huang, Y. H.; Ho, H. P.; Wu, S. Y.; Kong, S. K.
Abstract : Under certain conditions, a surface plasmon wave along a metal-dielectric interface can be excited by an optical beam. The reflected optical beam will then undergo changes in both intensity and phase. As the level of intensity or phase change is quite sensitive to the coupling conditions such as the molecule concentration on the metal surface, this phenomenon has been utilized for label-free detection of biological species and characterization of molecular interactions during the last two decades. Currently, most of the commercial surface plasmon resonance (SPR) sensors rely on the detection of absorption dip in angular or wavelength spectrum. However, recent researches have shown that phase detection has the potential to achieve lower limit of detection (LoD) and higher throughput. This paper, thus, intends to review various schemes and configurations for SPR phase detection. The performance advantages and disadvantages of various schemes will be emphasized. It is hoped that this paper will provide some insights to researchers interested in SPR sensing and help them to develop SPR sensors with better sensitivity and higher throughput.